PROSPECTS FOR THE DEVELOPMENT OF THE LABOR MARKET IN THE NEW SOCIO-ECONOMIC DEVELOPMENT - A.V. Trubina (Модернизация, инновация, развитие, 2016)
In article represented forecast of the main factors of the regional labor market: number of economically active population, the employed and unemployed population, levels of employment and unemployment with consider investment projects in Republic of Sakha (Yakutia) in two various(inertial and innovative forecasts) until 2030. Determined possible problems of future labor market and developed measures for their solving.